Do managers use a multi‐period, coordinated strategy involving accrual management choices and subsequent earnings forecasts to inflate expectations? - Billings, Bruce K.; Keskek, Sami; Myers, Linda A.; Omer, Thomas C. (Contemporary Accounting Research, 2025)
Abstract We provide evidence that some managers use a multi‐period, coordinated strategy involving inflated current‐period discretionary accruals and optimistic forecasts of future earnings to delay the revelation of bad news. Inflating discretionary accruals increases investor expectations of future performance, and issuing optimistic earnings forecasts of future earnings supports the inflated accruals and extends the horizon for managers to benefit. This strategy is more pronounced for firms that engage in earnings management outside of GAAP, suggesting intentional behavior. Our evidence indicates that managers use this coordinated strategy when firms experience significant bad news and cannot delay revealing all of the bad news through accrual management. We also find that managers use this coordinated strategy when focusing on short‐term performance due to career concerns (i.e., dismissal) or retirement or when they have shorter stock option vesting schedules, which motivates them to inflate investor expectations for shorter‐term personal benefits. Furthermore, managers using this strategy do not hold deep in the money exercisable stock options, which is consistent with managers' private assessment of a higher (lower) likelihood of releasing bad (good) news in the future.